Reversible Encephalopathy after Cardiac Transplantation: Histologic Evidence of Endothelial Activation, T-Cell Specific Trafficking, and Vascular Endothelial Growth Factor Expression - Horbinski, C.; Bartynski, W.S.; Carson-Walter, E.; Hamilton, R.L.; Tan, H.P.; Cheng, S. (American Journal of Neuroradiology, 2009)
SUMMARY: Reversible encephalopathy after transplantation is well recognized. The condition is commonly thought to be related to immune suppression, and a characteristic brain imaging pattern is typically recognized with vasogenic edema in the parietal and occipital regions, typically termed posterior reversible encephalopathy syndrome (PRES). We report the case of a patient with reversible encephalopathy after cardiac transplantation with brain biopsy evidence of endothelial activation, selective intravascular/perivascular T-cell trafficking, and VEGF expression in astrocytes, neurons, and the endothelium.